Removal of acrylic acid from process water using continuous adsorption - Airina, Zubir (2012)
Adsorption processes have been widely applied in chemical industry for water treatment,valuable compound recovery and undesired compound removal.Continuous adsorption using fixed bed adsorption column has shown its big roles in the large scale of industry.This research aims to study the acrylic acid removal from industrial process water by using continuous adsorption system.Three series of adsorption columns using coconut shell based activated carbon as adsorbent are employed in this study.The process water containing 4% acrylic acid was fed to the column.The adsorption removal efficiency for different feed flow rate through the column and different amount of the adsorbent were studied.The result shows the composition profile concentration of acrylic acid in the outlet flow of each column as a function of time.Therefore,this concludes that continuous adsorption of acrylic acid waste is favorably influenced by a feed flow rate and the weight of adsorbent. The improvement research study was proposed which it should test with high number of continuous column also increase height of bed with regeneration facility because the concentration is too high and the economic analysis can be carried out.